An initial systematic study of the linear energy transfer distributions of a proton beam under a transverse magnetic field. Issue 3 (11th February 2022) - Fujii, Yusuke; Ueda, Hideaki; Umegaki, Kikuo; Matsuura, Taeko
Abstract: Purpose: To evaluate the biological effectiveness of magnetic resonance (MR)‐guided proton beam therapy, comprehensively characterizing the dose and dose‐averaged linear energy transfer (LETd ) distributions under a magnetic field is necessary. Although detailed analysis has characterized curved beam paths and distorted dose distributions, the impact of a magnetic field on LETd should also be explored to determine the proton relative biological effectiveness (RBE). Hence, this initial study aims to present a basic analysis of LETd distributions in the presence of a magnetic field using Monte Carlo simulation (MCS). Methods: Geant4 MCS (version 10.1.p01) was performed to calculate the LETd distribution of proton beams. The incident beam energies were set to 70.2, 140.8, and 220 MeV, and both zero‐ and finite‐emittance pencil beams as well as scanned field were simulated. A transverse magnetic field of 0–3 T was applied within a water phantom placed at the isocenter, and the three‐dimensional dose and LETd distributions in the phantom were calculated. Then, the depth profiles of LETd along the curved trajectory and the lateral LETd profile at the Bragg peak (BP) depth were analyzed under changing energies and magnetic fields. In addition, for zero‐ and finite‐emittance beams, the correlation of the lateral asymmetries between the dose and LETd distributions were analyzed. Finally, spread‐out Bragg peak (SOBP) fields were simulated to assess the depth‐dependent asymmetry of the LETd distributions. Results: A transverse magnetic field distorted the lateral LETd distribution of a pencil beam at close to the BP, and the magnitude of the distortion at the BP increased for higher energy beams and larger magnetic fields. For a zero‐emittance beam, the differences in LETd between the left and right D20 positions were relatively large; the difference in LETd was 1.5 and 2.3 keV/μm at 140.8 and 220 MeV, respectively, at a magnetic field of 1.5 T. These asymmetries were pronounced at positions where the dose asymmetries were large. The size of the asymmetry was less substantial for a finite‐emittance beam and even less for a scanned field. However, a 1.5‐keV/μm difference still remained between the left and right D20 positions of a scanned field penumbra for a 220 MeV beam under the same magnetic field. For the SOBP field, it was found that the distal region of SOBP had the highest LETd distortions, followed by the central and proximal regions for the middle‐sized SOBP (5 × 5 × 5 cm 3 ), whereas the degree of LETd distortion did not vary much with depth for the 10 × 10 × 10‐cm 3 SOBP field. Conclusion: Our results indicate that not only the dose but also LETd distortions should be considered to accurately evaluate the biological effectiveness of MR‐guided proton beam therapy.